The burden of stomach cancer in indigenous populations: a systematic review and global assessment. Issue 1 (23rd October 2013) - Arnold, Melina; Moore, Suzanne P; Hassler, Sven; Ellison-Loschmann, Lis; Forman, David; Bray, Freddie
Abstract : Objective: Stomach cancer is a leading cause of cancer death, especially in developing countries. Incidence has been associated with poverty and is also reported to disproportionately affect indigenous peoples, many of whom live in poor socioeconomic circumstances and experience lower standards of health. In this comprehensive assessment, we explore the burden of stomach cancer among indigenous peoples globally. Design: The literature was searched systematically for studies on stomach cancer incidence, mortality and survival in indigenous populations, including Indigenous Australians, Maori in New Zealand, indigenous peoples from the circumpolar region, native Americans and Alaska natives in the USA, and the Mapuche peoples in Chile. Data from the New Zealand Health Information Service and the Surveillance Epidemiology and End Results (SEER) Program were used to estimate trends in incidence. Results: Elevated rates of stomach cancer incidence and mortality were found in almost all indigenous peoples relative to corresponding non-indigenous populations in the same regions or countries. This was particularly evident among Inuit residing in the circumpolar region (standardised incidence ratios (SIR) males: 3.9, females: 3.6) and in Maori (SIR males: 2.2, females: 3.2). Increasing trends in incidence were found for some groups. Conclusions: We found a higher burden of stomach cancer in indigenous populations globally, and rising incidence in some indigenous groups, in stark contrast to the decreasing global trends. This is of major public health concern requiring close surveillance and further research of potential risk factors. Given evidence that improving nutrition and housing sanitation, and Helicobacter pylori eradication programmes could reduce stomach cancer rates, policies which address these initiatives could reduce inequalities in stomach cancer burden for indigenous peoples.